2007
DOI: 10.1590/s1517-83822007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of gutta-percha cones with chlorhexidine

Abstract: This study investigated the effectiveness of detergent and aqueous solutions of 2% chlorhexidine digluconate in decontaminating gutta-percha cones (gpc) contaminated with bacteria, yeast, or bacterial spores. Guttapercha cones were contaminated with 10 7 -10 8 colony-forming units per milliliter (cfu/ml) of the following test organisms: Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, or Candida albicans. Spores of Bacillus subtilis were also tested. Contaminated gpc were treated with the chlorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 30 publications
0
12
0
7
Order By: Relevance
“…In fact, both aqueous and detergent solutions of 2% chlorhexidine were reported to be effective in decontaminating gutta-percha cones contaminated by Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Candida albicans and spores of Bacillus subtilis after 5 minutes of exposure. 3 Cardoso et al 10 also reported that gutta-percha cone decontamination may be achieved with 2% chlorhexidine after 1 minute. On the other hand, Gomes et al 8 showed that 0.2%, 1%, and 2% chlorhexidine, in either liquid or gel form, were not effective for the high disinfection requirements of gutta-percha cones contaminated with spores of B. subtilis, even after 72 hours of contact.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, both aqueous and detergent solutions of 2% chlorhexidine were reported to be effective in decontaminating gutta-percha cones contaminated by Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Candida albicans and spores of Bacillus subtilis after 5 minutes of exposure. 3 Cardoso et al 10 also reported that gutta-percha cone decontamination may be achieved with 2% chlorhexidine after 1 minute. On the other hand, Gomes et al 8 showed that 0.2%, 1%, and 2% chlorhexidine, in either liquid or gel form, were not effective for the high disinfection requirements of gutta-percha cones contaminated with spores of B. subtilis, even after 72 hours of contact.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,3,4,5,6 In clinical practice, the dentist is occasionally faced with the problem of re-infection after endodontic treatment. Moreover, penetration of bacteria into the blood stream of systemically compromised patients should be prevented because of the risk of infective endocarditis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations